MENANAMKAN RASA KEBERSAMAAN DAN SIKAP SALING MENGHARGAI MELALUI PEMBELAJARAN IPS DI SD KELAS AWAL TEMA 7 "KEBERSAMAAN" KELAS 2 SD - Alwasi, Farina Trias; Mujahidah, Idah; Rustini, Tin; Arifin, Muh Husen (Jurnal Penelitian dan Pendidikan IPS, 2023)
Cultivating the value of togetherness and mutual respect is an aspect of character education held in schools, in accordance with Permendikbud Number 21 of 2016 concerning Content Standards for Elementary and Secondary Education which states that core competencies and competencies in primary and secondary school education must include character education which includes attitudes spiritual, social attitudes, knowledge and skills. In this case, the integration of social studies learning into thematic learning in early grades is the main thing because social studies learning contains character values. So the purpose of this study is to foster the value of togetherness and mutual respect with students through integrated social studies learning in the student book theme 7 "Kebersamaan" for grade 2 SD, so that students with this are expected to gain insight into the differences that occur in society and can develop their social skills optimally. The source of data collection carried out in research is through library research. Literature studies are carried out by reading, understanding, studying, and reviewing a topic that is sourced from a 2nd grade elementary school student's book Theme 7 "Kebersamaan", journals, scientific articles, and so on related to the topic of the problem to be discussed. The results of this study indicate that by carrying out social studies learning integrated into thematics in elementary schools can help foster an attitude of togetherness and mutual respect in students.